ANALYSIS OF MOTOR ABILITES OF FOOTBALL AT PLAYERS AT DIFFERENT LEVELS COMPETITION - Omer Špirtović; Danilo Aćimović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The study was conducted on a sample of 170 respondents, players - seniors, aged 18-27 years, from areas of Montenegro. System was applied 16 variables of motor skills. Research objective was to determine the discriminatory ability of their rank accord¬ing to modalities which belong tested players (second and third league competition). Discriminant analysis results indicate that the motor variables are tested athletes in relation to the level of competition significantly different.